Economic impact of HIV and AIDS on the business process outsourcing and offshore contact centre industry in South africa - McCreanor, Christopher Paul Andrew (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.